(untitled) (Acta Scientiarum. Biological Sciences, 2012)
This study evaluated the physiological, morphological and ethological effects of salinity variations on the tropical zoanthid Protopalythoa variabilis. This zoanthid was submitted to different salinity levels to probe the hypothesis of osmoregulation. Specimens collected in beach rocks from Northeastern Brazil were taken alive to the laboratory in their original water. The osmoregulatory ability of P. variabilis can be determined by measuring the hemolymph osmolality under various salinity conditions and comparing with the osmolality of the medium. The zoanthid P. variabilis is a “weak regulator”, as it only osmoregulates within a narrow range of external salinity values, and its hemolymph osmolality drops, approximately in parallel with the isosmotic line, when the medium salinity falls below a certain limit. Ethological and morphological modifications under different salinities are discussed. This experiment shows for the first time the importance of osmotic regulation in the tropical zoanthid P. variabilis.